Crystal structure dependent tensile properties of silicone rubber: Influence of aluminium hydroxide - Ying Lin; Yuhao Liu; Kangning Wu; Liming Wang; Jianing Wang; Lijian Ding (Polymer Testing, 2022)
Aluminium hydroxide (ATH) filled silicone rubber working in a wide temperature range has to experience the crystallization process in many cases, in which mechanical properties would change greatly and its safety operation is threatened. In this paper, the structure-tensile properties relationship study of ATH filled silicone rubber from melting to crystallized state was carried out. By the differential scanning calorimetry (DSC) and broadband dielectric spectroscopy (BDS), it was found that ATH promoted heterogeneous nucleation in silicone rubber. With the increase of ATH, the proportion of rigid amorphous phase decreases. Meanwhile, the over doped ATH reduces the perfection of crystals during isothermal crystallization at −60 °C. Consequently, the elongation at break of high-content ATH filled silicone rubber with less crystalline and rigid amorphous phase dropped sharply by about 97% due to the failure of lamellae slips, which should arouse great attention for safety operation of ATH filled silicone rubber. It is thereby suggested to take the elongation at break as one of the criteria for the selection of ATH filled silicone rubber used in extremely low temperature.